A new high‐resolution melting assay for genotyping Alternaria species causing citrus brown spot. (14th April 2018) - Garganese, Francesca; Ippolito, Antonio; di Rienzo, Valentina; Lotti, Concetta; Montemurro, Cinzia; Sanzani, Simona M
Abstract: BACKGROUND: Alternaria brown spot is one of the most important diseases of tangerines and their hybrids worldwide. To set up effective control strategy, the accurate detection and identification of the species responsible for the diseases is crucial. However, characterization based on morphology and/or multilocus genetic approaches is time consuming, requires great expertise and sometimes is not conclusive. Therefore, the set‐up of a rapid and efficient DNA‐based assay might be of paramount importance. High‐resolution melting (HRM) analysis represents an interesting tool for the uncovering of nucleotide variations as small as one base difference and, as such, relevant to species characterization. RESULTS: In the present investigation, an HRM assay based on the Alternaria barcoding region OPA1–3 was set up. Specimen strains of the main citrus‐associated Alternaria species and morphotypes generated distinct and normalized profiles, allowing their differentiation when HRM‐tested. Moreover, when the assay was used to screen an Alternaria collection from citrus fruit and leaves, it distributed the 180 isolates in three independent clusters, readily and consistently resolved. Isolates were identified as belonging to the species Alternaria alternata and the species complex A. arborescens . Within A. alternata, the morphotypes alternata (77% of the collection) and limoniasperae (17% of the collection) were present. CONCLUSIONS: Although further validation experiments will be performed to optimize the assay for a diagnostic use, this HRM approach might represent a rapid, sensitive and specific method for the detection and identification of Alternaria spp. responsible for citrus brown spot disease. © 2018 Society of Chemical Industry